Effectiveness Of Green Human Resources Management Practices On Manufacturing Companies Cikarang - Ramadhan, Fardhal Virgiawan (BIMA Journal (Business, Management, & Accounting Journal), 2023)
Green Human Resources Management (GHRM) is one of the practices for development and maintenance in order to have a significant impact on the preservation of the surrounding environment. Cikarang is one of the areas that has more than 2,125 companies in various industries such as manufacturing and others, so there is a need for awareness in GHRM. This research establishes 5 (five) GHRM indicators in the form of green recruitment and selection, green job analysis and design, green training and development, green performance management and green reward management. This study aims to explain and analyze the effectiveness of GHRM practices in manufacturing companies in Cikarang, Indonesia. The research method used is a qualitative approach with online ethnography. Sources of data in this study by collecting primary and secondary data and conducting in-depth interviews and conducting focus group discussions. The results in this study are that manufacturing companies in Cikarang, Indonesia have implemented green recruitment and selection, manufacturing companies in Cikarang, Indonesia have not implemented green job analytics and design, manufacturing companies in Cikarang, Indonesia have implemented green training and development, manufacturing companies in Cikarang, Indonesia have implemented green performance management, and manufacturing companies in Cikarang, Indonesia have not implemented green reward management.